Leadership Transformation Implication in Bojonegoro Regency - Amanda Setiorini; Tuty Sariwulan; Saparuddin Mukhtar (Journal of Social Science, 2022)
The election of outstanding regional heads brings hope for the future of leadership in Indonesia. One of the regional heads is the Regent of Bojonegoro for the 2008–2018 period. This study aims to determine the implementation of leadership that can bring changes to public organizations such as the Government of Bojonegoro Regency. By using qualitative methods and case study approaches, this research seeks to reduce Suyoto's leadership experience to the essence of implementing leadership needed by public organizations. Through codification using NVivo, ten themes were found, namely looking for solutions or innovative, pro-people, good characters, not being distant, having a forgiving nature, being caring, visionary, being a public bus driver, listening to feedback, and being a role model. The results show that leaders need to have the right traits and skills, which are based on the drive to serve. This result should be imitated by other regions in choosing their leaders. But the difficulty lies in the urge to serve, because the urge is not obvious from the very beginning of the election of a leader, but will be tested once the leader gains power.